Understanding the paradox of surviving childhood trauma : techniques and tools for working with suicidality and dissociation - Zucchetto, Joanne (New York, NY : Routledge, 2019)
Understanding the Paradox of Surviving Childhood Trauma offers clinicians a new framework for understanding the symptoms and coping mechanisms displayed by survivors of childhood abuse. This approach considers how characteristics such as suicidality, self-harm, persistent depression, and anxiety can have roots in behaviors and beliefs that helped patients survive their trauma. This book provides practitioners with case examples, practical tips, and techniques for applying this mindset directly to their most complex cases. By depathologizing patients' experiences and behaviors, and moving beyond simply managing them, therapists can reduce their clients' shame and work collaboratively to understand the underlying message that these behaviors conceal.
OCLC-licensed vendor bibliographic record.
Keywords: Psychic trauma in children -- Treatment; Suicidal behavior -- Treatment; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Psychotherapy / General